2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6
3y+5=y-25 2y=-30 y= -15
5y = 3y + 12 5y - 3y = (3y - 3y) + 12 2y = 12 y = 6
5x-2y+3z-2x-y-4z=3x-3y-z
X + 3y - 2y + 3y = X + (3-2+3)y = X + 4y
2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6
3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8
For y - 2y - 3y equals 0, y equals 0.
y = -1
4n + 3y
80 = 3y + 2y + 4 + 1 75 = 5y 15 = y y = 15
3y+5=y-25 2y=-30 y= -15
It is y+3y-2y = 2y simplified
y = 8.6
-3y + y = -2y
5y = 2y+9 5y-2y = 9 3y = 9 y = 3
Solving for y: 5y = 9 + 2y 5y - 2y = 9 3y = 9 y = 9/3 = 3